2005
DOI: 10.1016/j.jcrs.2005.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Artisan–Verysise aphakic lens implantation

Abstract: Artisan-Verysise IOL implantation seems a safe, predictable, and effective option for aphakic eyes without capsule support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
64
3
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(84 citation statements)
references
References 25 publications
(22 reference statements)
10
64
3
7
Order By: Relevance
“…Severe hyperopia developed in only one eye. However, postoperative refractive error was more than previous reports of either Artisan IOL 1,7,12 or iris fixated PCIOL. 13 One reason might be inaccurate keratometry in most of our cases due to irregular astigmatism caused by previous repaired corneoscleral laceration.…”
Section: Complicationscontrasting
confidence: 60%
See 2 more Smart Citations
“…Severe hyperopia developed in only one eye. However, postoperative refractive error was more than previous reports of either Artisan IOL 1,7,12 or iris fixated PCIOL. 13 One reason might be inaccurate keratometry in most of our cases due to irregular astigmatism caused by previous repaired corneoscleral laceration.…”
Section: Complicationscontrasting
confidence: 60%
“…Except The Artisan IOL have been used safely for secondary implantation in adults and children with aphakia. 1,7,[9][10][11][12] They have also been used after traumatic injuries to the globe. [9][10][11][12] Gü ell et al 7 reported satisfactory results of Artisan IOL implantations in 16 aphakic patients.…”
Section: Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of IOL implantation in the absence of capsule support have been satisfactory in general when viewed with respect to visual results and recovery [9][10][11][15][16][17][18][19][20], although few trials appear to show that anterior chamber IOLs provide a superior visual recovery than scleral-fixated PCIOLs [21][22][23]. The cause for the poorer visual recovery with sclera-fixated PCIOLs is represented by microscope light-induced retinal injuries, due to the prolonged operating time compared with anterior chamber implants [12,24].…”
Section: Discussionmentioning
confidence: 99%
“…The use of Artisan-Verysise intraocular lens for secondary implantation and correction of aphakia has been estimated to be safe, also achieving a BCVA of 20/40 or better in 37.5% of eyes treated by Güell et al; corneal endothelial cell loss was mainly observed within the first year (7.78%), whereas cystoid macular oedema was diagnosed in two out of a total of 16 patients in a follow-up of at least 3 years (28). A customized PMMA iris print and iris-clipped AC IOL (Ophtec BV) has been proposed to repair aniridia along with correction of aphakia and corneal astigmatism (29).…”
Section: Outcomes and Complications Following Implantation Of Ac Iolsmentioning
confidence: 99%